Mathematical knowledge for teaching: Adding to the description through a study of probability in practice - Kazima, Mercy; Adler, Jill (Pythagoras, 2011)
In their description of the mathematical work of teaching, Ball, Bass & Hill (2004) describe the mathematical problem solving that teachers do as they go about their work. In this paper we add to this description through our study of teaching of probability in a grade 8 multilingual classroom in South Africa. We use instances of teaching to highlight the mathematical problem solving that teachers might face as they work with learners’ ideas, both expected and unexpected. We discuss the restructuring of tasks as an inevitable feature of teachers’ work, and argue that in addition to scaling up or scaling down of the task as Ball et al. (2004) describe, restructuring can also entail shifting the mathematical outcomes from those intended. We also point out how well known issues in mathematics education, for example working with learners’ everyday knowledge, and the languages they bring to class, are highlighted by the context of probability, enabling additional insights into the mathematical work of teaching.
KerkoCite.ItemAlsoKnownAs: 10.4102/pythagoras.v0i63.108 4752638:CYP5HS6S
Keywords: _C:Malawi MWI